The Role of the SC/ST Act in addressing Caste-Based Atrocities: A Critical Legal Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The SC/ST Act, or Scheduled Castes and Scheduled Tribes (Prevention of Atrocities) Act, 1989, was passed with the intention of ending the long-standing prejudice and brutality against India's most vulnerable populations. Karnataka has a long history of caste-based violence; this article examines the SC/ST Act's implementation and effects in that state. This study synthesizes previous research to examine three primary areas: the Act's legislative and policy structure, the socio-legal obstacles to its implementation, and the historical background of caste-based violence. There has to be strong legislative safeguards like the SC/ST Act since caste-based prejudice is deeply rooted in Karnataka's history, especially in rural regions. Although the Act is a major step forward in India's legal system, there are obstacles to its execution, such as victims not being adequately represented in court and crimes not being reported. Studies conducted in Karnataka provide light on ongoing problems with the justice system and police enforcement, which are worsened by societal shame and the fear of reprisal. Despite these obstacles, the court and civil society groups have been crucial in protecting the rights of SCs and STs, bringing attention to the issue, and providing legal remedies. The research finds that the SC/ST Act may be a strong weapon against caste-based crimes, but that it would only work in Karnataka if the social and legal obstacles to its implementation are removed. If the Act is to achieve its goal of safeguarding disadvantaged populations in Karnataka and abroad, more study and innovative policymaking are required.